Pengaruh Tenaga Kerja Terhadap Pembiayaan Kur Tahun 2019 di Pulau Jawa - Adi , Tony Margiyanto; Gayatri, Askardiya Mirza (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of labor on People's Business Credit (KUR) investment in Java Island in 2019. The analysis reveals that labor has a very small and insignificant impact on the amount of KUR investment. This is evidenced by a beta coefficient value of -0.003, which is close to zero, and a low correlation. In other words, the contribution of labor to the level of KUR investment is minimal. Although there is a weak positive relationship between labor and KUR investment, partial and part correlation tests indicate that the influence of labor is almost undetectable when other factors, such as KUR absorption, are considered. These findings suggest that labor is not a key variable in determining KUR investment levels in this region. This study provides valuable insights for policymakers to focus more on other significant factors that drive KUR investment growth, such as optimizing KUR fund absorption and improving access to capital for small and medium enterprises.